PERSEBARAN GEOGRAFI JENIS-JENIS Pimelodendron (EUPHORBIACEAE) DI MALESIA - Tutie Djarwaningsih (BERITA BIOLOGI, 2002)
The analysis of geographical distribution of Pimelodendron in Malesia based especially on data from the revision study of Pimelodendron (Euphorbiaceae) in Malesia. An analysis of distribution indicated that the highest number of species can be recognized, i.e. in Sumatera four species P.griffithianum, P. macrocarpum. P. zoanthogyne, and P. yatesianum; Peninsular Malaysia and Borneo have three species P. griffithianum, P. macrocarpum, and P. zoanthogyne; while Celebes, Moluccas, Lesser Sunda Islands, New Guinea, Solomon Islands and tropical Australia have one species (P. amboinicum). The geographical distribution indicated that the Malesian region can be considered as the centre of distribution of Pimelodendron.